Produktivitas Pustakawan Perpustakaan Nasional Sebagai Penulis Artikel: Studi Kasus Pada Jurnal Media Pustakawan dan Visi Pustaka - Agus Wahyudi; Jusa Junaedi (Media Pustakawan, 2021)
This study aims to analyze Perpusnas librarian’s productivity in producing scientific paper published in Visi Pustaka and Media Pustakawan from 2010-2019. The results of this research are expected to provide information to Perpusnas to be used as one of the references in the development of Perpusnas librarian’s expertise, especially in scientific writing. This research is a descriptive study with a quantitative approach. The sampling technique used was saturated samples. The collected data were processed using Microsoft Office Excel. The productivity picture is obtained by comparing the number of articles written by Perpusnas librarians with the total number of articles. The search results of articles in the journal Visi Pustaka and Media Pustakawan published on 2010-2019 obtained data of 450 articles written by 316 different authors with details 48 writers from Perpusnas librarian, 7 writers from non-librarian Perpusnas employees, and 261 other writers from outside Perpusnas. There is 1 National Library librarian who is the most productive in producing articles with a total of 9 articles. Meanwhile, the most productive non-librarian Perpusnas employee produced 7 articles. If measured by comparing the number of articles published in the journal Media Pustakawan and Visi Pustaka during the 2010-2019 published period, the Perpusnas librarian’s productivity are around 16.44% of the total articles. The annual increase or decrease of Perpusnas librarians is not always followed by an increase or decrease of articles written by Perpusnas librarians.